Cutaneous Erythema at Scar Site of Modified Radical Mastectomy: An Unexpected Manifestation of Recurrent Carcinoma - Awrad Mohammed-Reda Nasralla; Mohammed Abdulirazzaq Al-Duhileb; Ali Jamal-Aldein Arini; Samir Sami Amr (Case Reports in Surgery)
A 44-year-old woman presented with marked erythema over right mastectomy scar, while on Herceptin therapy. She had neoadjuvant chemotherapy, modified radical mastectomy, and radiotherapy less than one year earlier for the treatment of invasive ductal carcinoma. On physical examination, no palpable masses were detected in the erythematous skin. A biopsy revealed permeation of the skin lymphatics by emboli of metastatic ductal carcinoma, similar to what is seen in inflammatory carcinoma. The involved skin was excised, followed by immediate reconstruction with transverse rectus abdominis muscle (TRAM) flap. On follow-up, the wound was healing well, with no signs of inflammation.